2021
DOI: 10.1039/d1sc03724b
|View full text |Cite
|
Sign up to set email alerts
|

Ternary complexes of chiral disulfonimides in transfer-hydrogenation of imines: the relevance of late intermediates in ion pair catalysis

Abstract: In ion pairing catalysis, the structures of advanced intermediates are often not accessible. Here, we present a combined experimental and computational study of ternary complexes in Brønsted acid catalysis, which show unexpected H-bond switching.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 57 publications
0
19
0
1
Order By: Relevance
“…As can be seen from Scheme , the oxidation potentials of common organic single-electron reductants [ E ox o (XH 2 )] span a very large range about 2.777 V [∼64.0 kcal/mol] from −2.298 V [ E ox o (H • )] to 0.479 V [ E ox o (HEH 2 )] . Since HEH 2 has always been used as a classical electron donor in chemical reactions, especially the photocatalytic reaction, HEH 2 is assigned as a medium strong electron donor. Compared with common organic single-electron reductants (−2.298 to 0.479 V), all YH – (−0.350 to −0.134 V) with lower oxidation potentials have strong electron-donating abilities, even better than HEH 2 (0.479 V) and BNAH (0.219 V) …”
Section: Resultsmentioning
confidence: 99%
“…As can be seen from Scheme , the oxidation potentials of common organic single-electron reductants [ E ox o (XH 2 )] span a very large range about 2.777 V [∼64.0 kcal/mol] from −2.298 V [ E ox o (H • )] to 0.479 V [ E ox o (HEH 2 )] . Since HEH 2 has always been used as a classical electron donor in chemical reactions, especially the photocatalytic reaction, HEH 2 is assigned as a medium strong electron donor. Compared with common organic single-electron reductants (−2.298 to 0.479 V), all YH – (−0.350 to −0.134 V) with lower oxidation potentials have strong electron-donating abilities, even better than HEH 2 (0.479 V) and BNAH (0.219 V) …”
Section: Resultsmentioning
confidence: 99%
“…Next, we studied the binary complex of CPA and hydrazone by NMR at low temperature. Previously, we were able to obtain structural information about CPA and DSI binary and ternary complexes with imines [32–34] . Thus, we prepared a CPA C1 /( E )‐ 1 a 1 : 1 complex in CD 2 Cl 2 and acquired NMR spectra at 233 K. At this temperature, acid‐promoted isomerization is stopped.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we were able to obtain structural information about CPA and DSI binary and ternary complexes with imines. [32][33][34] Thus, we prepared a CPA C1/(E)-1 a 1 : 1 complex in CD 2 Cl 2 and acquired NMR spectra at 233 K. At this temperature, acid-promoted isomerization is stopped. Two distinct hydrogen bond signals emerged in a 1 : 1 ratio (δ H 12.87 and 9.60 ppm), corresponding to the two NH sites of the protonated hydrazone.…”
Section: Cyclization Reactionmentioning
confidence: 99%
“…Thus far, this report has only focused on the ( Z )-isomer of methylethylideneimine as past studies on reductive amination using organic hydride donors found that the ( Z )-isomer was more kinetically favored than the ( E )-isomer due to a decrease in steric hindrance for the hydride attack. , Our own DFT calculations align with these studies, as it was found that hydride transfer to the ( Z )-isomer of the iminium was slightly kinetically favored by 0.4 kcal/mol over the ( E )-isomer.…”
Section: Resultsmentioning
confidence: 99%